Phytochemical Evaluation And In Vitro Study Of Antioxidant Potency Of Amorphophallus Campanulatus, Alocasia Indica And Colocasia Esculenta: A Comparative Analysis - SUBHASHREE BASU,; ANURUPA SEN,; MOUMITA DAS,; PRANABES NATH,; GOURIPROSAD DATTA, (International Journal of Pharma and Bio Sciences, 2012)
Amorphophallus campanulatus, Alocasia indica and Colocasia esculenta are very popular for their edible corms and leaves, especially in Assam and Bengal and are cultivated there as common food crops. Besides, they are also considered as medicinal plants in Sushruta Samhita and Ayurveda. So, the ethanolic extracts of these tubers were screened for the presence of in vitro antioxidant potential against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical, ferric reducing power, hydroxyl radical and superoxide radical. Total phenolic and flavonoid contents of all the extracts were also evaluated. The results revealed that the ethanolic extracts of all the tubers possessed antioxidant property. Among the three, Amorphophallus campanulatus showed significantly higher (P<0.01) antioxidant potential in scavenging free radical than that of Alocasia indica and Colocasia esculenta. This higher ability to scavenge free radicals by Amorphophallus campanulatus may be attributed to the presence of higher amount of polyphenols and flavonoids in it, than the other two tubers as evidenced from our result. Thus the ethanolic extracts of these tubers can be utilized in future as therapeutic agent against free radical induced oxidative stress.